Underground architects of modern pop music: A core collection - Bell, Thomas W. (My University, 2008)
In the summer of 2006 a new music course was launched at Youngstown State University, Underground Architects of Modern Pop Music. The course was a survey of unsung composers, experimentalists, and bands that although commercially unsuccessful by music industry standards, have proven since to be powerfully influential. The artists examined created music for its own sake and recorded and released their music on small, independent labels. In some cases they recorded in their own living rooms or basements, fostering the DIY (Do it yourself) ethic that is now transforming the music business as we know it. The course began with a consideration of the pop music industry, how “hits” are manufactured, the double-edged nature of copyright, and payola. This set the stage for analytical, critical listening, both to the innovators who were virtually unknown at the time and to the chart-topping hits of the time. The contrast between the two was profound and prompted much and vigorous discussion. What emerged is a bibliography of essential recordings, monographs, and DVDs representative of the most influential, “under the radar” artists from the late 1960’s to the early 1990’s, a core collection. Students and scholars in music and an array of interdisciplinary fields will benefit immensely from exposure to the innovations and inventions of the artists and material included here.
A discography of unsung musical innovators from 1968-1988.
Keywords: Underground; Rock music; Pop music